2018
DOI: 10.3389/fpsyg.2018.02324
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Self-Directed Learning Skills of Undergraduate Students

Abstract: The aims of this study were to reveal university students' self-directed learning skills and determine whether these skills vary based on university type, gender, field of study, year of study, academic success, type of university entrance score, income level, and the desire to pursue a graduate degree. Also, this study explored the relationship between university students' self-directed learning skills and their lifelong learning tendencies. The study group of the survey comprised 2,600 first and fourth-year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
101
2
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 181 publications
(152 citation statements)
references
References 38 publications
5
101
2
10
Order By: Relevance
“…For example, female students are found to be more ambivalent about technology and less interested in using technology while male students are more interested and experienced in using technology (Cassidy & Eachus, 2012). However, Grover (2015) found that gender is not a hindrance to the learning process and does not make a significant difference in e-learning. The results of the same study by Tekkol & Demirel (2018) on higher education students in South Korea found that the understanding and readiness of internet use among male students was not significant compared to female students.…”
Section: Literature Reviewmentioning
confidence: 95%
See 4 more Smart Citations
“…For example, female students are found to be more ambivalent about technology and less interested in using technology while male students are more interested and experienced in using technology (Cassidy & Eachus, 2012). However, Grover (2015) found that gender is not a hindrance to the learning process and does not make a significant difference in e-learning. The results of the same study by Tekkol & Demirel (2018) on higher education students in South Korea found that the understanding and readiness of internet use among male students was not significant compared to female students.…”
Section: Literature Reviewmentioning
confidence: 95%
“…Students' demographics play an important role in determining students' understanding and readiness for e-learning and the obstacles in e-learning (Grover, 2015). Some studies indicate that there are differences between genders in technology use.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations